There is an alternative: Challenging the logic of neoliberal penality. (November 2014) - Bell, Emma
This article seeks to sketch out alternatives to neoliberal penality by seeking to undermine the four institutional logics of neoliberalism as identified by Loïc Wacquant (2009). It begins by critically analysing the potential value of public criminology as an exit strategy, suggesting that whilst this approach has much value, popular versions of it are in fact rather limited on account of their exclusion of offenders themselves from the debate and their optimism about the capacity of existing institutions to challenge the current punitive consensus. It suggests that a genuinely 'public' criminology should be informed by an abolitionist stance to both current penal policies and the neoliberal system as a whole. This may be the best means of truly democratizing penal politics.